A state of the art review in crop residue burning in India: Previous knowledge, present circumstances and future strategies - Asik Dutta; Abhik Patra; Kali K. Hazra; Chaitanya P. Nath; Narendra Kumar; Amitava Rakshit (Environmental Challenges, 2022)
Sustainable management of surplus paddy residue in the Indo-Gangetic plain is a back-breaking task for farmers due to lack of viable options. Eventually, farmers prefer to incinerate it mindlessly. Sustainable residue management is important because paddy straws are rich in nutrients and can be translated into value added products. Several important reasons like short time span for sowing wheat, limited farm mechanisation, scarce manpower and poor acceptability of paddy straw as fodder are the root causes behind this residue burning. The aim of this paper is to find the fundamental causes behind this illicit practice and mark the harmful effects of residue burning on ecosystem. This manuscript also deciphers in depth strategies, environmental laws, socio-economic policy frameworks and future thrusts which would offer multifaceted avenues for the sustainable management of crop residues. Losses of essential nutrients from the soil and in the residue, along with emission of potential greenhouse gases (GHGs) are the major repercussions of this mal-practice. Adaption and commercialisation of resource conservation technologies like conservation agriculture (CA) with low silica content in rice varieties are excellent opportunities to look after. Value addition by preparation of compost, mushroom production, biogas/oil generation, and producing energy in the power plants are new avenues to convert this waste into wealth. Respective state and central government along with different private organisations are working hand in hand to spread awareness and control stubble burning. Fostering the current technologies through policy interventions and organising training camps in the village level with monetary incentives are the important strategies to look for.